Attitudes and beliefs of Eastern European consumers towards piglet castration and meat from castrated pigs. (February 2020) - Tomasevic, Igor; Bahelka, Ivan; Čandek-Potokar, Marjeta; Čítek, Jaroslav; Djekić, Ilija; Djurkin Kušec, Ivona; Getya, Andriy; Guerrero, Luis; Iordăchescu, Gabriela; Ivanova, Sonya; Nakov, Dimitar; Sołowiej, Bartosz G.; et al.
Abstract: Castration of male piglets is a common practice to avoid boar taint but is being questioned. The present work has an exploratory character and aims to investigate the beliefs and attitudes of Eastern European consumers regarding boar taint, surgical castration immunocastration and perception of meat from castrated pigs and to find out possible segments of consumers regarding these attitudes and beliefs. For this purpose, a consumer study was carried out involving 5508 consumers from 13 Eastern European countries (Bosnia and Herzegovina, Bulgaria, Czech Republic, Croatia, North Macedonia, Hungary, Moldova, Poland, Romania, Serbia, Slovakia, Slovenia and Ukraine). The questionnaire included statements related to beliefs about castration and perception of meat from castrated pigs, attitudes towards meat from castrated pigs. Results show that in general beliefs and attitudes of the consumers are not defined, probably because of the lack of knowledge (information was not provided to the consumers) towards these issues. Three different clusters of consumers were obtained with different beliefs towards castration. Highlights: Beliefs and attitudes towards castration in Eastern Europe were explored. Low knowledge of castration might explain lack of definition of beliefs/attitudes. 47% of consumers were classified as "against castration". 31% of consumers were classified as "indifferent towards castration". 22% of consumers were classified as "pro-castration".